IMPLEMENTASI PASAL 29 UNDANG – UNDANG NOMOR 46 TAHUN 2009 TENTANG PEMBATASAN WAKTU PENYELESAIAN PERSIDANGAN TINDAK PIDANA KORUPSI DI PENGADILAN NEGERI PALEMBANG KLAS 1A KHUSUS - Meidianti, Silfi; Nofianti, Liza (Justici, 2023)
ABSTRACT Completion of corruption cases in corruption cases as stipulated in Article 29 of Law Number 46 of 2009 concerning the Corruption Court which states: "Corruption cases are examined, tried and decided by the first level Corruption Court in a maximum period of 120 (one hundred and two thirty working days from the date the case was transferred to the Corruption Crime Court. Nevertheless according to practice, the provisions of Article 29 of Law No. 46 of 2009, it cannot be fully implemented. Problems Why is there a limitation on the time to complete the examination of cases of corruption in Article 29 of the Republic of Indonesia Act No.46 of 2009 concerning Court of Criminal Acts of corruption. And what is the consequence of the juridical to the settlement of cases that exceed the time limit specified in article 29 of the Republic of Indonesia Act No.46 of 2009 concerning the Court of Criminal Acts of corruption? The research method is Empirical Juridical in this study the purpose of analyzing the problem is done by integrating legal materials with primary data is data obtained from the first source such as interviews and documentation in the Palembang District 1A Class Court, while secondary data is data obtained from library materials. Based on Article 29 the case of corruption is examined, tried and decided by the first level of the Corruption Court within a maximum of 120 (one hundred and twenty) working days from the date the case is transferred to the Corruption Court, to provide legal certainty for justice seekers , Encouraging an increase in the performance of judges in examining, adjudicating, and deciding cases, as well as suppressing the accumulation of court cases at all levels of the judiciary, which if not implemented will raise the presumption that the panel of judges do not have the ability to resolve cases in a timely fashion and judicial stigma. There is a need for close commitment and cooperation between law enforcement officers namely, Judges, Public Prosecutors and Legal Counsels.